2015
DOI: 10.1186/s12888-015-0455-4
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric dimethylarginine in somatically healthy schizophrenia patients treated with atypical antipsychotics: a case–control study

Abstract: BackgroundSchizophrenia is associated with increased cardiovascular morbidity and mortality. Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of the nitric oxide synthase, and the L-arginine:ADMA ratio are markers of endothelial dysfunction that predict mortality and adverse outcome in a range of cardiovascular disorders. Increased ADMA levels may also lead to increased oxidative stress. We hypothesized that ADMA and the L-arginine:ADMA ratio are increased in somatically healthy schizophrenia patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
1
6
1
1
Order By: Relevance
“…There was also a statistically significant difference between the control group compared to clozapine receiving schizophrenia patients and the no-drug group in terms of ADMA, and this is consistent with the study of Das (24), Celik (19), and Zincir (22). However, the study of Jorgensen et al (14) showed no difference between various groups.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…There was also a statistically significant difference between the control group compared to clozapine receiving schizophrenia patients and the no-drug group in terms of ADMA, and this is consistent with the study of Das (24), Celik (19), and Zincir (22). However, the study of Jorgensen et al (14) showed no difference between various groups.…”
Section: Discussionsupporting
confidence: 86%
“…In another study, short-term treatment initially creates a protection against endothelial damage which may be due to reduced agitation and activity of the autonomic nervous system, but no significant association was found between the disease severities (9). This study showed that drug consumption is a factor which increases possible risk factors in heart disease (14).…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations